(untitled) (Journal of Architectural Design, 2022)
The hats of Karakalpak women are radically different from the hats of fraternal peoples. The Kazakh people wear white headscarves, and Karakalpak women wear floral headscarves of different colors. The young girls wore a doppia and a small handkerchief (must be red). The adult girls combined the prison with Aydin and pulled her hair to the left because it was wrapped around her head. She is wearing a big scarf